From Bench to Bedside to Bug: An Update of Clinically Relevant Advances in the Care of Persons with Helicobacter pylori Associated Diseases - N Chiba; ABR Thomson; P Sinclair (Canadian Journal of Gastroenterology)
In-depth meetings of the XIth International Workshop on Gastroduodenal Pathology and Helicobacter pylori led to the presentation and discussion of extensive new data on H pylori and its diseases. The mode of transmission of H pylori remains unclear, and it remains unknown why only a small proportion of infected individuals develop duodenal or gastric ulcer disease and even fewer develop gastric cancer. The role of H pylori eradication in persons with uninvestigated dyspepsia remains controversial. New clinical trials of H pylori treatment show symptom relief and improvement in the quality of life of persons with functional dyspepsia, especially in those with ulcer-like or reflux-like dyspepsia. Clearly the move is toward symptom-based management of persons with dyspepsia, with fewer endoscopies being needed in the otherwise healthy young dyspeptic patients. It remains controversial whether eradicating H pylori in duodenal ulcer or functional dyspepsia increases the risk of subsequent development of gastroesophageal reflux disease. The one-week proton pump inhibitor-based triple regimens remain the gold standard of H pylori therapy, but some of the ranitidine bismuth citrate plus two antibiotic regimens also achieve an 80% H pylori eradication rate on an intention-to-treat basis. While the urea breath test remains the noninvasive test of choice, interesting new data are available on the use of stool antigen testing to diagnose H pylori infection. The number of H pylori-associated gastroduodenal diseases grows to include possible liver, vascular, immune and skin conditions.